2017
DOI: 10.1161/strokeaha.116.014816
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oxidized Low-Density Lipoprotein With Prognosis of Stroke and Stroke Subtypes

Abstract: Background and Purpose-The association between oxidized low-density lipoprotein (oxLDL) and the long-term prognosis of stroke is unclear. The aim of this study is to investigate whether oxLDL levels contribute to the prognosis of stroke and stroke subtypes. Methods-All patients with ischemic stroke were recruited from the SOS-Stroke (Study of Oxidative Stress in Patients WithAcute Ischemic Stroke) and classified into 5 different subtypes, according to the TOAST criteria (Trial of Org 10172 in Acute Stroke Trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 33 publications
(27 reference statements)
2
29
0
2
Order By: Relevance
“…Tsai et al [13] revealed that higher oxLDL concentration was a predictor for poor prognosis at 3 months after acute ischaemic stroke. The Study of Oxidative Stress in Patients With Acute Ischemic Stroke (SOS-Stroke) also demonstrated that high levels of oxLDL were associated with high risk of death and poor functional outcome at 1 year after stroke onset [14]. Our study confirmed and extended previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Tsai et al [13] revealed that higher oxLDL concentration was a predictor for poor prognosis at 3 months after acute ischaemic stroke. The Study of Oxidative Stress in Patients With Acute Ischemic Stroke (SOS-Stroke) also demonstrated that high levels of oxLDL were associated with high risk of death and poor functional outcome at 1 year after stroke onset [14]. Our study confirmed and extended previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Oxidized low‐density lipoprotein (oxLDL) is a biomarker that is a key factor for the occurrence and development of atherosclerosis and the formation of unstable plaque . Its pathological role in atherosclerosis has been recognized , with oxLDL causing endothelial cell injury and promoting foam cell formation, the proliferation of vascular smooth muscle cells, and platelet adhesion and aggregation, as well as other factors involved in the formation of atherosclerosis . oxLDL has also been designated as an independent risk factor in many acute or chronic inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed that LDL‐C and its oxidized form was an independent risk factor of stroke (Cholesterol Treatment Trialists’ (CTT) Collaboration, ; Wang et al., ). In our study, LDL‐C weakly correlated with the outcome of AIS ( p = .038) with an unadjusted OR of 1.377 (95% CI, 1.018–1.865), while, serum sLOX‐1 showed strong relation with clinical prognosis of AIS ( p < .0001) with an adjusted OR of 2.946 (95% CI, 1.788–4.856).…”
Section: Discussionmentioning
confidence: 99%